Recent Advancements in Stimuli-Responsive Polymeric Implants Fabricated via Additive Manufacturing: A Review - Kothawade, Sachin; Singh, Sudarshan (Current Pharmaceutical Design, 2026)
This review discusses the latest progress in using smart polymeric materials for making medical implants with advanced three-dimensional (3D) and four-dimensional (4D) printing techniques. These smart polymers, also known as stimuli-responsive polymers, can change their properties when exposed to external triggers like temperature, pH, light, or magnetic fields. Integrating these materials with 3D/4D printing allows the creation of highly customizable and functional implants that can adapt to the body's environment. This means implants can now perform additional tasks, such as releasing drugs or changing shape when needed. The review covers different 3D/4D printing methods, the types of smart polymers available, and the benefits of using these materials in medical implants. It also addresses the challenges faced in developing these advanced implants, such as finding suitable materials that are safe for the body and ensuring precise manufacturing. The future prospects of these innovative implants are promising, with potential applications in personalized medicine and non-invasive treatments. This review aims to provide a detailed analysis of recent advancements in stimuli-responsive polymeric materials utilized in additive manufacturing of medical implants. The objective is to explore these materials' clinical implications, address the unique challenges in their development and fabrication, and outline their future potential in enhancing personalized and non-invasive medical treatments.
Keywords: stimuli-responsive materials